Effects of westbound trans-meridian travel on countermovement jump performance in international-level rowers - Everett, K. L.; Chapman, D. W.; Mitchell, J. A.; Ball, N. (The Journal of Strength and Conditioning Research, 2022)
International long-haul air travel is a necessity for many athletes as part of their training or competition schedules. However, long-haul travel is also associated with impaired neuromuscular function. An athlete's lower body neuromuscular status is frequently assessed and monitored using countermovement jump (CMJ). This study assessed the impact of westbound trans-meridian travel on changes in CMJ performance in highly trained aerobic athletes. Highly trained male rowers (n = 21, 23.7 ± 1.4 years, 1.91 ± 0.07 m, 86.9 ± 9.9 kg) undertook a westbound flight incurring 22 hours of flight time with 30 hours of total travel time across 9 time zones. Athletes completed a single set of 6 loaded CMJ repetitions before and after travel with performance measured using a digital optical encoder attached to a 20 kg barbell. Each CMJ repetition was assessed for mean concentric velocity, jump height (JH), eccentric displacement, JH:dip ratio, mean power, and mean eccentric velocity, with comparisons made between mean set changes before and after travel. Changes were compared using a one tail paired t-test and characterized using Cohen's d (95% confidence interval) effect sizes. Significance was accepted at p = 0.05. Small-to-moderate changes were observed in all variables following westbound travel. These changes may be because of retention of high training loads before travel resulting in the athletes being in a fatigued state, whereas travel time worked as a forced recovery period. Reductions in CMJ performance are likely following westbound travel, however, may be affected by training fatigue before travel that may confound CMJ performance as a monitoring metric.